Early Childhoods’ Artistic Creativities In Fisheries Community, Tambak Lorok Semarang - Budiartati, Emmy (Universitas Negeri Semarang, 2016)
This study tried to gain comprehensive understanding (holistic and contextual) re- garding the development of the arts in early childhood in fishing communities of Tambak Lorok Semarang. Specifically, the study was developed in order to find a clear and factual picture of the development of artistic creativity in early childhood and forms of parents’ participation in the implementation of the development of artistic creativity in early childhood. The approach used in this study to explore the various sources of data is qualitative descriptive approach, to provide a picture of the reality on the subject study objectively. This study is limited by time and place, and the cases studied in the form of events and activities of individuals. The results showed 1) the limited of teachers understanding regards the artistic creativity that can be taught remember that early childhood is the golden age of creative expression. 2) Many obstacles in Paud Nanda Sifana developing various teaching methods to develop artistic creativity. 3) The role of parents towards children education in the Tambak Lorok neighborhood still limited, it can be seen from the less cooperation between teachers and parents in educating children, the parents assume that the school or the teacher is the only party who in charge on the children education.